PARTICIPATION OF THE WOMEN’S ASSOCIATION OF UZBEKISTAN OF "OLIMA" IN SUPPORTING THE PARTICIPATION OF YOUNG WOMEN AND GIRLS IN SCIENCE - Mavlanova Sitora Sheraliyevna (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, based on the fact that the development of society in today’s era of globalization is directly related to the participation of young women and girls with high scientific potential, the importance of the role of young women and girls in the field of science, in this regard, the women’s association "Olima" in Uzbekistan Its importance and importance, its founding history, and its activities in supporting young women and girls’ aspirations for education are presented. Also, the author mentioned in this article about the cooperation of "Olima" association with some foreign organizations.